Reliability of personality and values tests: The effects of "high stakes" selection conditions, and of four years in medical school. (4th May 2019) - Fukui, Yuriko; Noda, Saeko; Okada, Midori; Mihara, Nakako; Bore, Miles; Munro, Don; Powis, David
Abstract: This study investigated if scores on tests of personal qualities are affected by whether they will determine selection decisions ("high stakes") or not; and whether they are stable for individuals and groups across a four-year medical course. Two tests, one assessing values and one assessing components of personality, were administered either at the same time as a medical university entrance exam (first cohort; N = 216), or after entry was confirmed (second cohort; N = 142). Both cohorts took the tests again after four years of medical school. Analysis of variance was used to compare group mean scores and interactions, and correlation coefficients to measure temporal reliability. The high stakes cohort initially presented themselves in a significantly more positive light on the personality test. After four years of medical school scores on both tests changed significantly, towards more communitarian values and less empathic attitudes. Thus, personality scores were affected by both the conditions under which the initial tests were conducted and by the passage of time, but values only by the passage of time. Before and after scores were significantly correlated.